Deteksi Embrio Ayam Berdasarkan Citra Grayscale Menggunakan K-means Automatic Thresholding - Paulus Harsadi (STMIK Sinar Nusantara, 2014)
Image segmentation is a basic operation for the next image analysis process. Thresholding is one of segmentations technique commonly used to separate the object with the background. Thresholding technique in this paper is used to detect the chicken embryo from the egg observation image (candling eggs) those are fertile or infertile. The main problem in the thresholding technique is to determine the threshold value. In the paper, we propose the use of k-means automatic thresholding method to determine the best threshold value, so that the maximum achievable object segmentation are reached. It is expected to support this process to determine whether the chicken egg hatching process is fertile or infertile. Keywords-component; image processing; automatic threshold, grayscale image, candling eggs;